Profit Management Detection During The Enforcement Period Hillization of Mineral and Coal - Retno WIDIASTUTI; Anna ISROWIYAH; Triesti CANDRAWATI; Fita SETIATI (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This study examines the earnings management activities carried out by companies during the mineral and coal downstream period. The object of the study is oil, gas, and coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2020-2023, with a total population of 284 observations. The sampling technique is purposive sampling, with the results of 200 observations. The data collection method used is documentation. Data analysis in this study by calculating the value of discretionary accruals using the performance-matched discretionary accrual measures calculation method by Kothari et al. (2005). The results showed that all companies carried out earnings management actions. The percentage of companies that carried out earnings management by decreasing income was 54.5%, while the remaining 45.5% did income increase. This condition illustrates that management is still making various efforts to make financial reports look as attractive as stakeholders desire. This research provides input to the government to consider the impact of mineral and coal downstream policies on related industries.